Chilling at the grassroots? The impact of the Leveson Inquiry on journalist-source relations and the reporting of the powerful at local level. (1st March 2017) - Morrison, James
No sooner had the Leveson Inquiry opened in 2011 than journalists and politicians were warning of a 'chilling effect' on the willingness of the press to continue using informal avenues to research stories. A particular fear was that tougher regulation might deter newspapers from using off-the-record briefings – and occasional subterfuge – to legitimately investigate public-interest issues that would go unreported if they relied solely on official channels. But a wider concern was that a putative 'Leveson effect' could also discourage both journalists and sources from engaging in the day-to-day communications on which newspapers relied for routine content. Drawing on first-hand testimony from practising local journalists, this article argues that, while there is early anecdotal evidence for some chilling at the grassroots, this is affecting sources more than journalists. Moreover, their concerns are based on a (perhaps wilful) 'scapegoating' of Leveson for other factors hampering their relations with reporters: notably, longer-term institutional moves to regulate their relations with journalists and, perhaps more significantly, financial cutbacks.